MISAPPROPRIATION OF FUNDS: BRINGING PUBLIC TRUST ON TAHFIZ INSTITUTIONS VIA EFFECTIVE FINANCIAL ACCOUNTING AND REPORTING PRACTICES - Suzana San; Siti Dalina Tumiran@ Kamal Nasser; Rosliza Abu Bakar; Syuhaila Razak; Nik Zam Nik Wan (International Journal of Accounting, Finance and Business, 2022)
Tahfiz Institutions (TIs) are Islamic institutions that aim to produce students who are able to memorize the Al-Quran, practice the knowledge of Islam in their life, have good attitude and abide by the rules and regulations in Al-Quran and As-Sunnah. Nowadays TIs received wider acceptance as an Islamic education centre and has received encouraging responses from society. More than 91% of the TIs in Malaysia are privately owned either by foundations, non-government organisations or individuals. Their sources of funds usually come from tuition and school fees as well as donations and sponsorship by the public at large, individuals, non-government organisations (NGOs), Islamic Council, private and public companies and organisations. Regrettably, despite its function to inculcate moral values among students, misappropriation of funds among TIs management themselves had been reported and the possibility of more being unreported cannot be denied as well. The majority of the significant factors underlying the aforementioned issues are poor financial management and mismanagement of funds. Stakeholder theory can be used to explain the concept of accountability for TIs because they are accountable to a variety of stakeholders such as regulators, donors, parents, and students. The focus of this conceptual paper is to identify appropriate financial accounting and reporting practices that may be used by TIs in order to be held equitably accountable for the funds that they have received. The presence of financial control practices can ensure financial integrity of TIs and disregard the bad claims being reported earlier. By effectively implementing financial accounting and reporting practices and disclosing information about its fund management on a regular basis, it will boost transparency and instil public confidence in the organisation to solicit additional donations in the future.